2020
DOI: 10.1001/jamadermatol.2020.0352
|View full text |Cite
|
Sign up to set email alerts
|

Association of Afamelanotide With Improved Outcomes in Patients With Erythropoietic Protoporphyria in Clinical Practice

Abstract: rythropoietic protoporphyria (EPP) (OMIM 177000) is a rare inherited disorder of heme biosynthesis, causing painful photosensitivity. 1 Erythropoietic protoporphyria is caused by FECH or ALAS2 gene mutations, leading to protoporphyrin IX accumulation in erythroid cells. 2,3 It severely affects patients' quality of life (QoL) 4 by causing severe pain after light exposure, which lasts several days and is unresponsive to analgesics. 2,5 This results in sunlightavoiding behavior, limiting daily and social activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 19 publications
4
39
0
Order By: Relevance
“…The limitations of our study lie in the retrospective and observational nature of the study design and the limited number of participants. However, such a design is considered suitable in ultra-rare conditions such as EPP and is often used in post-admission surveillance for noxious side effects [ 28 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of our study lie in the retrospective and observational nature of the study design and the limited number of participants. However, such a design is considered suitable in ultra-rare conditions such as EPP and is often used in post-admission surveillance for noxious side effects [ 28 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most frequently reported were nausea, fatigue, flushing, and nausea with headache. No related serious adverse events occurred during the study [72]. Skin hyperpigmentation is the most prominent visible effect of afamelanotide; some patients reported increased skin pigmentation and darkening of preexisting nevi and ephelides.…”
Section: Post-marketing Surveillancementioning
confidence: 90%
“…Patients were also treated with 16 mg afamelanotide implants with a minimum interval of 60 days, max four implants per year. This observational study, based on the EMA requested PASS protocol, demonstrated clinically significant, and sustained, positive effects on quality of life (an improvement of 14% on the EPP QoL), increased reported duration of light exposure with an added 6.1 hours per week and less painful phototoxic reactions [72]. Recently, a study was published introducing the new endpoint phototoxic burn protection factor (PBTT) for assessing treatment effect in EPP.…”
Section: Observational Studiesmentioning
confidence: 91%
“…To improve the quality of life of the patients for several diseases, the management of symptoms and pain is of utmost importance ( 35 , 36 ). Likewise, for PP, a constant challenge prevails in daily life to avoid the pain that leads to reduced quality of life ( 37 ). Moreover, analgesic drugs fail to relieve the pain in PP ( 31 ).…”
Section: Discussionmentioning
confidence: 99%